2020
DOI: 10.1088/1757-899x/862/4/042001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing energy efficiency factors in industrial companies

Abstract: The relevance of the study is due to the fact that changes in the energy management policy at the national level, rising energy prices and increased state environmental control over production prompt industry to develop effective organizational and technical solutions in the field of energy management. The aim of the study is to identify energy management factors that determine the success or failure of the implementation of energy efficiency measures in industrial companies. In the empirical part of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This should be supported by good collaboration starting within the company and involving marketing, production planning, inventory control, production, utilities, etc. [41]. A stable workload for the production department will ensure op timal and efficient performance of the produc tion process, utility, and energy.…”
Section: Discussionmentioning
confidence: 99%
“…This should be supported by good collaboration starting within the company and involving marketing, production planning, inventory control, production, utilities, etc. [41]. A stable workload for the production department will ensure op timal and efficient performance of the produc tion process, utility, and energy.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, we determine the efficiency of using primary energy resources in the production of thermal energy [6]. Since the consumption of heat energy in the enterprise is made from several (from the centralized network, renewable and non-renewable) energy sources in the territory of the enterprise, we will combine them into one source, that is, we will consider it as a hybrid heat energy source consisting of several energy sources [6]. To do this, we write the (3) expression in the following form:…”
Section: Methodsmentioning
confidence: 99%
“…6 shows that authors from 41 countries published reports relating to reliability and performance in the maintenance during the period 2014-2020. The nationality distribution of 110 technology-related papers in numbers and showed that the main contributors are from the United States (27), followed by China (18); Germany (10); United Kingdom (9); South Korea (8); Australia (7); Iran (6); Brazil, France, and Italy (5 each); Belgium, India, and Norway (4 each); Canada, Malaysia, Denmark and Sweden (3 each); Turkey, Belgium, Netherlands, Poland, Romania, and Spain (2 each); Argentina, Belgrade, Colombia, Czech Republic, Finland, Indonesia, Ireland, New Zealand, Pakistan, Russian, Saudi Arabia, Scotland, Slovakia, South Africa, Georgia, Slovenia, Japan and Algeria (1 each).…”
Section: Distribution By Nationalitymentioning
confidence: 99%
“…Lack of intelligent integration of performance and poor automation in the maintenance of power plants causes losses that are roughly 2.5 times higher than those attributed to hardware failure [4]. In terms of maintenance, personnel performance is closely related to energy management performance, and is thus a factor in energy consumption and human errors [5,6], although further investigation is required to determine the interaction between personnel, energy management, and the critical success factors (CSFs) associated with thermal and gas power plant maintenance [7].…”
Section: Introductionmentioning
confidence: 99%